Design a 12 v to 24 v DC-DC switching boost converter / \c Kee Cheng Rui - Kee Cheng Rui (School of Electrical Engineering, University Malaysia Perlis, 2011)
This purpose of this project is to present the design and analysis boosting DC voltage from 12 V to 24 V by using a MOSFET and LM555 integrated circuit design specifically for this task. The PSIM, MATHCAD or equivalent software are used to simulate the ideal boost converter.